Effect of ruminal acidosis and short-term low feed intake on indicators of gastrointestinal barrier function in Holstein steers. (29th January 2018) - Pederzolli, Rae-Leigh A; Van Kessel, Andrew G; Campbell, John; Hendrick, Steve; Wood, Katie M; Penner, Gregory B
Abstract: The objective of this study was to determine effect of ruminal acidosis (RA ) and low feed intake [LFI ] on the regional barrier function of the gastrointestinal tract. Twenty-one Holstein steers were fed for ad libitum intake for 5 d (control [CON] ), fed at 25% of ad libitum intake for 5 d (LFI), or provided 2 d of ad libitum intake followed by 1-d of feed restriction (25% of ad libitum intake), 1 d where 30% of ad libitum dry matter intake (DMI) was provided as pelleted barley followed by the full allocation (RA) and fed for ad libitum intake the following day. Tissues and digesta from the rumen, omasum, duodenum, jejunum, ileum, cecum, proximal, and distal colon were collected. Permeability was assessed using the mucosal-to-serosal flux of inulin ( J MS-inulin ) and mannitol ( J MS-mannitol ). Digesta pH was 0.81, 0.63, and 0.42 pH units less for RA than CON in the rumen, cecum, and proximal colon; while, LFI had pH that was 0.47 and 0.36 pH units greater in the rumen and proximal colon compared to CON. Total ruminal short-chain fatty acid (SCFA ) concentration were less for LFI (92 mM; P = 0.010) and RA (87 mM; P = 0.007) than CON (172 mM) steers. In the proximal colon, the proportion of butyrate ( P = 0.025 and P = 0.022) and isobutyrate ( P = 0.019 and P = 0.019) were greater, and acetate ( P = 0.028 and P = 0.028) was less for LFI and RA, respectively, when compared to CON steers. Ruminal papillae length, width, perimeter, and surface area were 1.21 mm, 0.78 mm, 3.84 mm, and 11.15 mm 2 less for LFI than CON; while, RA decreased papillae width by 0.52 mm relative to CON. The J MS-mannitol was less for LFI steers than CON in the proximal colon ( P = 0.041) and in the distal colon ( P = 0.015). Increased gene expression for claudin 1, occludin, tight-cell junction protein 1 and 2, and toll-like receptor 4 were detected for LFI relative to CON in the rumen, jejunum, and proximal colon. For RA steers, expression of toll-like receptor 4 in the rumen, and occludin and tight-cell junction protein 1 were greater in the jejunum than CON. An acute RA challenge decreased pH in the rumen and large intestine but did not increase tissue permeability due to increases in the expression of genes related to barrier function within 1 d of the challenge. Steers exposed to LFI for 5 d had reduced ruminal SCFA concentrations, smaller ruminal papillae dimensions, and increased tissue permeability in the proximal and distal colon despite increases for genes related to barrier function and immune function.